UiTM Global News : Engaging the world (Vol.2 / August 2019) - UiTM, Office of International Affairs (Office of International Affairs, 2019)
In this issue, with the Merdeka spirit in the air, we feature more new global partners and an increasing number of collaborations. Under our new leadership, UiTM is expanding its horizon strategically on less charted territories, especially in the Middle East and East Asia. The expansion is leading to an increasing number of partnerships, international engagements and research initiatives. There is an increasing level of confidence displayed by our new partners, as they realise that UiTM can provide access for them to grow globally. UiTM takes these opportunities to engage and be visible on the world stage. We also highlight prominent news such as international achievements of UiTM staff and students, international initiatives with Better Futures Consortium, Summer and Exchange Programmes, visits by international partners, and feature events in 2019.